Substance use and older people - Crome, Ilana B.; Wu, Li-Tzy.; Crome, Peter; Rao, Rahul (Chichester, West Sussex, UK : Ames, Iowa : John Wiley & Sons Inc., 2014)
Substance use and addiction is an increasing problem amongst older people. The identification of this problem is often more difficult in older patients and is frequently missed, particularly in the primary care context and in emergency departments, but also in a range of medical and psychiatric specialties.Substance Use and Older People shows how to recognise and treat substance problems in older patients. However, it goes well beyond assessment and diagnosis by incorporating up-to-date evidence on the management of those older people who are presenting with chronic complex disorders, which result from the problematic use of alcohol, inappropriate prescribed or over the counter medications, tobacco, or other drugs. It also examines a variety of biological and psychosocial approaches to the understanding of these issues in the older population and offers recommendations for policy.Substance Use and Older People is a valuable resource for geriatricians, old age psychiatrists, addiction psychiatrists, primary care physicians, and gerontologists as well as policy makers, researchers, and educators. It is also relevant for residents and fellows training in geriatrics or geri-psychiatry, general practitioners and nursing home physicians.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Substance-Related Disorders; Aged; Middle Aged; Older people -- Drug use; POLITICAL SCIENCE / Public Policy / Social Security; POLITICAL SCIENCE / Public Policy / Social Services & Welfare; Older people -- Drug use; Medical; Electronic books